DESIGNING RISK-ORIENTED SYSTEM OF INTERNAL CONTROL AND AUDIT IN LARGE CORPORATION (illustrated by the public company Russian Railways) - Oleg B. Ivanov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses principles and practice of building a united risk-oriented system of internal control and audit in the public company Russian Railways, which can become a vital tool of company management and an important condition for ensuring efficiency of its economic functioning, finance stability, increasing investment appeal and dynamic development. The system is built on the basis of corporate standards with due regard to best world practice, Russian experience and requirements of global finance regulators. The practice of struggling against corruption and in-house fraud is being analyzed.